2010
DOI: 10.1186/1471-2407-10-653
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of women with basal-like ductal carcinoma in situ of the breast: a population-based cohort study

Abstract: BackgroundMicroarray gene-profiling of invasive breast cancer has identified different subtypes including luminal A, luminal B, HER2-overexpressing and basal-like groups. Basal-like invasive breast cancer is associated with a worse prognosis. However, the prognosis of basal-like ductal carcinoma in situ (DCIS) is still unknown. Our aim was to study the prognosis of basal-like DCIS in a large population-based cohort.MethodsAll 458 women with a primary DCIS diagnosed between 1986 and 2004, in Uppland and Västman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 38 publications
0
27
2
Order By: Relevance
“…Of our cohort of DCIS, 33.7 % were identified to be basal-like. This differs from the reported rates of basal-like DCIS from studies by Livasy et al [48] at 8.0 %, Zhou et al [46] at 8.2 %, and Clark et al [45] at 4.2 %. This difference may be due to the higher sensitivity of 34bE12, which targets 4 cytokeratins (CK1, 5, 10, and 14).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Of our cohort of DCIS, 33.7 % were identified to be basal-like. This differs from the reported rates of basal-like DCIS from studies by Livasy et al [48] at 8.0 %, Zhou et al [46] at 8.2 %, and Clark et al [45] at 4.2 %. This difference may be due to the higher sensitivity of 34bE12, which targets 4 cytokeratins (CK1, 5, 10, and 14).…”
Section: Discussioncontrasting
confidence: 81%
“…The rate of triple-negative DCIS in our study was noted to be at 7.1 %, which does not differ greatly from the findings of Clark et al [45] and Zhou et al [46], whose documented rates of triple-negative DCIS were 7.5 and 7.8 %, respectively. We observed a higher proportion of triple-negative DCIS subtype in the symptomatic group compared to the screen-detected group.…”
Section: Discussioncontrasting
confidence: 33%
“…Using immunohistochemical markers (ER, PR, HER2, and Ki67), Sharaf Aldeen et al [25] classified 94 DCIS cases into five subtypes and found a similar distribution of molecular subtypes between black and white women. In addition, the basal-like DCIS defined by ER, PR, HER2, CK5/6, and EGFR displayed a comparable risk of IBTs to the other molecular subtypes [26]. Future efforts should focus on the clinical relevance of these findings and novel molecular markers that mediate poorer DCIS outcomes in black women.…”
Section: Discussionmentioning
confidence: 99%
“…While this could bias effect estimates of SNPs associated with disease aggressiveness or progression, shared risk profiles (3, 90, 91) and subtype distributions (1, 3, 92) suggest this bias would be small.…”
Section: Discussionmentioning
confidence: 99%